Body composition assessment with segmental multifrequency bioimpedance method - Salmi, J. A. (Journal of Sports Science & Medicine, 2003)
Body composition assessment is an important factor in weight management, exercise science and clinical health care. Bioelectrical impedance analysis (BIA) is widely used method for estimating body composition. The purpose of this study was to evaluate segmental multi-frequency bioimpedance method (SMFBIA) in body composition assessment with underwater weighing (UWW) and whole body dual energy x-ray absorptiometry (DXA) in healthy obese middle-aged male subjects. The measurements were carried out at the UKK Institute for Health Promotion Research in Tampere, Finland according to standard procedures of BIA, UWW and DXA. Fifty-eight (n=58) male subjects, aged 36-53 years, body mass index (BMI) 24.9-40.7, were studied. Of them forty (n=40) underwent also DXA measurement. Fat mass (FM), fat-percentage (F%) and fat free mass (FFM) were the primary outcome variables. The mean whole body FM (+SD) from UWW was 31.5 kg (±7.3). By DXA it was 29.9 kg (±8.1) and by SMFBIA it was 25.5 kg (±7.6), respectively. The Pearson correlation coefficients (r) were 0.91 between UWW and SMFBIA, 0.94 between DXA and SMFBIA and 0.91 between UWW and DXA, respectively. The mean segmental FFM (+SD) from DXA was 7.7 kg (±1.0) for arms, 41.7 kg (±4.6) for trunk and 21.9 kg (±2.2) for legs. By SMFBIA, it was 8.5 kg (±0.9), 31.7 kg (±2.5) and 20.3 kg (±1.6), respectively. Pearson correlation coefficients were 0.75 for arms, 0.72 for legs and 0.77 for trunk. This study demonstrates that SMFBIA is usefull method to evaluate fat mass (FM), fat free mass (FFM) and fat percentage (F%) from whole body. Moreover, SMFBIA is suitable method for assessing segmental distribution of fat free mass (FFM) compared to whole body DXA. The results of this study indicate that the SMFBIA method may be particularly advantageous in large epidemiological studies as being a simple, rapid and inexpensive method for field use of whole body and segmental body composition assessment.